Peran affective trust dalam hubungan antara platform work remuneration, fleksibilitas kerja, dan kinerja mitra pengemudi di Kota Semarang - Vina Khusnul Khotimah; Nanda Adhi Purusa; Artha Febriana; Masitha Fahmi Wardhani (Journal of Management and Digital Business, 2026)
The development of digital platform-based work systems increasingly emphasizes the importance of fairness in reward provision and flexibility in work arrangements for driver-partners. This study aims to analyze the effect of platform-based work rewards and work flexibility on partner performance, with affective trust as a mediating variable. This study used a quantitative approach through an explanatory survey design with 100 active driver-partners. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that platform-based work rewards and work flexibility have a positive influence on affective trust and driver-partner performance. In addition, affective trust shows a significant mediating role in explaining the relationship between the two variables and performance. These findings confirm that reward fairness and work flexibility play a significant role in building emotional trust and improving driver-partner performance in algorithm-based work systems.